Outcomes of Early Pars Plana Vitrectomy for Acute Post Operative Endophthalmitis with or without Silicone Oil - Farrukh Jameel, Hussain Ahmad khaqan, Abdul Hye, Saher Abdul Hye, Hassan Raza Chaudhary (Pakistan Journal of Ophthalmology, 2017)
Place and duration of study: Lahore General Hospital, Lahore from March 2011 to March 2016. Material and Methods: One hundred and twelve patients of acute post-surgical endophthalmitis were included in the study. Patients were randomized into two groups after no clinical improvement was seen post primary vitreous tap and intravitreal vancomycin and ceftazidime. In group 1 patients undergoing PPV with endotamponade (silicon oil) were included while in group 2 patients undergoing PPV without endotamponade were included. Study was divided in two phases. In first phase 30 patients underwent PPV without endotamponade and 30 patients with endotamponade. Considering the results of phase 1, rest of the 52 patients underwent PPV with endotamponade in phase 2. Removal of silicone oil in all patients was done at 12 weeks. Results: In first phase of study 23 (76.66%) patients in Group 2 showed retinal detachment within four weeks of follow up, while no patient (0%) in Group 1 showed retinal detachment within four weeks of follow up. Later 6 (7.31%) patients in group 1 showed retinal detachment within four weeks of silicone oil removal. In second phase all 52 patients showed no retinal detachment after undergoing PPV with endotamponade as in group 1. Overall 82 patients underwent PPV with endotamponade including first and second phase and only 6 patients got retinal detachment. Conclusion: Early PPV with endotamponade should be preferred to PPV without endotamponade in cases of acute postoperative endophthalmitis due to statistically significant improvement in anatomical and functional outcomes. Key words: Endophthalmitis, Pars plana vitrectomy, Endotamponade, Retinal Detachment, Silicone oil.